Pembangkitan Nilai Belief Pada Dempster-Shafer Dengan Particle Swarm Optimization (PSO) Untuk Penentuan Pasal Kasus Penganiayaan - Merry Gricelya Nababan; Rekyan Regasari Mardi Putri; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The crime against the body and life continues to increase every year, judges as decision makers against criminal defendants have a very important role in providing decisions. However, there are some things that the judge needs to consider in making decisions, so that the problem of uncertainty can be a judge's obstacle. The author applies a method that can solve the problem of this uncertainty is Dempster-shafer (D-S). D-S algorithm has belief value that serves to determine the influence between symptoms obtained from an expert. In this case the expert can not give the value of belief karana must be in accordance with the evidence and real sanctions. So with Particle Swarm Optimization algorithm (PSO) belief value will be raised as well as doing optimization to get maximum results. In accordance with the test conducted from the case data of the penganiaayan obtained maximum belief value based on PSO parameter test. The result of system accuracy calculation by using belief value that has been optimized with D-S on 29 cases of abuse shows accuracy of 13.79%. The result of this accuracy is not maximal due to complex problems with the output (Output) of the system more than one. For further research, we can use Artificial Neural Network (ANN) method or with algorithm Analytic Hierarchy Process (AHP).